Prevalence, Types of Medication errors and Barriers to Reporting Errors by Nurses in an Educational Hospital in Kermanshah - Maryam Mirzaei; Alireza Khatony; Roya Safari Faramani; Elham Sepahvand (Tehran University of Medical Sciences, 2014)
Background & Aim: The most common types of medical errors are medication errors. Medication errors can cause serious health problems and should be considered a threat to patients' safety. The aim of this study was to investigate the prevalence and types of medication errors and barriers to reporting errors by nurses in an educational hospital in Kermanshah University of Medical Sciences in 2012 .   Methods & Materials: In this cross-sectional study, 96 nurses working in an educational hospital were randomly selected to the study. Review of medication errors and reporting them over the last three months were assessed using a valid and reliable questionnaire. Data were analyzed using the SPSS-20.   Results: The prevalence of medication errors was 79.2%. The most common errors included giving oral drugs by mistake (53.1%) and medication later or earlier than the stipulated time (41.7%), respectively. Reporting the medication errors was 14%. Among the barriers to reporting the errors, barriers related to administrative issues were more highlighted than the staff relating barriers.   Conclusion: The results showed high prevalence of medication errors and low rates of error reporting. Holding periodic courses on safe medication and using management strategies to encourage nurses to report errors are recommended.